Lactiplantibacillus plantarum 1008 Enhances Testicular Function and Spermatogenesis via the Modulation of Gut Microbiota in Male Mice with High-Fat-Diet-Induced Obesity - Chin-Yu Liu; Yi-Wen Chen; Tsung-Yu Tsai; Te-Hua Liu; Ting-Chia Chang; Chih-Wei Tsao (Biology)
Our study was designed to investigate the Lactiplantibacillus plantarum 1008 (LP1008) on testicular antioxidant capacity, spermatogenesis, apoptosis, autophagy, and metabolic function in male mice with high-fat-diet-induced obesity. A total of thirty-six male C57BL/6 mice were fed a normal diet (denoted as the NC group) or a high-fat control diet (denoted as the HFC group) for 16 weeks, then half of the HFC group was randomly chosen and subsequently fed with LP1008 for the final 8 weeks (high-fat diet + LP1008; denoted as the HFP group). The HFP group expressed improved blood cholesterol, insulin resistance, hepatic function, and lipopolysaccharide (LPS) levels compared to the HFC group. Meanwhile, the HFC group displayed decreased testicular testosterone levels, sperm quality, and 17β-HSD protein expression, which were rescued after LP1008 treatment. Moreover, the HFC group had lower superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPX) enzyme activities. After LP1008 treatment, enhanced antioxidative activities and decreased lipid peroxidation were observed. The HFC group also exhibited aggravated apoptosis, inflammation, and autophagy proteins in the testis, which were ameliorated by LP1008 supplementation. Furthermore, the gut microbiota analysis results revealed that the Firmicutes/Bacteroidetes ratio was significantly elevated in the HFC and HFP groups compared to the NC group and that LP1008 treatment diminished Ruminococcaceae and enhanced Bifidobacteriaceae diversity. In summary, LP1008 treatment strengthened antioxidative enzyme levels and regulated microbiota-ameliorated HFC-induced oxidative stress, apoptosis, inflammation, and autophagy, and thus improved testicular function and semen quality.